Clinical presentations of nontuberculous mycobacteria as suspected and drug-resistant tuberculosis: Experience from a tertiary care center in Eastern India - Sivasankar Das; Baijayantimala Mishra; Prasanta Raghab Mohapatra; Chappity Preetam; Sutapa Rath (International Journal of Mycobacteriology, 2022)
Background: Nontuberculous mycobacteria (NTM) are on the rise worldwide. The diagnosis and treatment of NTM disease create a dilemma for physicians as their clinical features often overlap with that of tuberculosis (TB). The present study aims to report a series of NTM infections presenting as suspected TB. Methods: It was a prospective observational study starting from December 2018 to January 2022. A total of 1850 suspected TB patients (pulmonary = 522 and extrapulmonary = 1328) were included in this study. Clinical features, radiological findings, microbiological diagnosis, treatment, and outcome were recorded. Clinical specimens were processed for Ziehl–Neelsen staining, GeneXpert MTB/Rif assay by cartridge-based nucleic acid amplification test, and culture. The culture-positive isolates were categorized as Mycobacterium tuberculosis complex or NTM depending on the detection of MPT64 antigen by immunochromatographic test. The NTM isolates were speciated by line probe assay using GenoType® Mycobacterium common mycobacteria kit. The criteria of the American Thoracic Society/Infectious Diseases Society of America were applied to confirm NTM disease. Results: Of 1850 suspected TB patients, NTM disease was diagnosed in 20 patients (pulmonary = 9, nonpulmonary = 11). Eight NTM cases presented as suspected drug-resistant-TB with a history of antitubercular therapy. Among pulmonary NTM cases, Mycobacterium scrofulaceum (n = 7) was the most common species followed by Mycobacterium kansasii (n = 1) and Mycobacterium intracellulare (n = 1). In nonpulmonary cases, Mycobacterium abscessus (n = 8) was involved in majority of cases followed by Mycobacterium fortuitum (n = 3). Cavitary lung disease and laparoscopic port site infections were most frequent pulmonary and non-pulmonary manifestations respectively. Conclusion: Hence, there is an urgent need for better diagnostic and drug susceptibility testing facility along with standardized treatment protocol for NTM disease.